The influence of accounting information systems, internal controls, and work motivation on employee performance in savings and loan cooperatives in Bengkulu city - Septi Aufa, Popy; Aprila, Nila (Jurnal Ekonomi, 2024)
This research aims to determine the influence of accounting information systems, internal controls, and work motivation on employee performance in Savings and Loan Cooperatives in Bengkulu City. The study utilizes a quantitative approach, with primary data collected through the distribution of questionnaires to respondents, specifically employees working in Savings and Loan Cooperatives in Bengkulu City. The total number of employees in these cooperatives is 70. The purposive sampling method is employed to select a sample of 45 individuals for this research. The analysis method used is multiple linear regression analysis supported by the SPSS program. The findings of this research reveal that accounting information systems and work motivation positively influence employee performance in Savings and Loan Cooperatives in Bengkulu City. However, internal controls do not have a significant impact on employee performance in these cooperatives.